Endotracheal tube complication during extubation following surgical repair of a traumatic tracheal laceration. Issue 2 (15th April 2020) - Miller, Lucy; Pryke, Sam; Panti, Ambra; Gozalo Marcilla, Miguel
Abstract : Difficult or impossible tracheal extubation has previously been reported in the veterinary literature as a result of endotracheal tube (ETT) faults or due to their entanglement with oesophagostomy tubes. Inadvertent transfixation of the ETT to the trachea during oral–maxillofacial surgery is a reported cause of extubation complications in the human literature. In this case, an incident of accidental ETT cuff transfixation to the trachea of a dog undergoing surgical repair of a traumatic tracheal laceration is reported. General anaesthesia for tracheal surgery requires special consideration of airway management to reduce complications. While precautions can be taken to avoid ETT placement within the surgical field, this cannot always be avoided and measures should be implemented for detection of transfixation. If tracheal extubation complications do arise, it is important to consider the differential causes and act quickly to resolve the problem and ensure minimal distress to the animal.